Femur Hoffa fracture. A case report - Aynaguano-Perez, Edison; Ortiz, Marcelo; Guerrero, Bolivar; Proaño, Patricio (Revista Colombiana de Ortopedia y Traumatología, 2020)
Unicondylar coronal plane fractures of the distal third of the femur are known as Hoffa fractures, are uncommon and rather rare. Only few cases of this type of fracture have been reported worldwide. By definition they are unstable fractures and therefore require surgical resolution. The mechanism of trauma in this type of fracture is an anterior to posterior direct trauma with a flexed knee. They can often go unnoticed on the anterior-posterior (AP) radiographic projection, so it is important to carefully evaluate the lateral projection. When they are suspected or perhaps evident, it is necessary to perform a computerized axial tomography (CT)in order to clearly define both, the characteristics of the fracture itself as the surgical resolution options, since the approach and the fixation method are controversial. Although nowadays the availability and characteristics of the different types of implants have increased, there is no consensus about the way to manage these fractures in medical literature, mainly due to the lack of expertise in these rare cases. Evidence Level: IV